Dilated cardiomyopathy secondary to acute pancreatitis caused by hypertriglyceridemia - Greer, Jordan W (J Surg Case Rep, 2018)
A 30-year-old male presented to an outside facility with acute pancreatitis and triglycerides of 1594. He was transferred to our facility after becoming febrile, hypoxic and in acute renal failure with triglycerides of 4243. CT scan performed showed wall-off pancreatic necrosis. He underwent continuous renal replacement therapy and his acute renal failure resolved. He was treated with broad spectrum antibiotics and discharged. He developed a fever to 101 a week later and was found to have a large infected pancreatic pseudocyst. This was managed with an IR placed drain. This was continued for 6 weeks. He came to the emergency department several weeks later with shortness of breath and 3+ edema to bilateral lower extremities and lower abdomen. TTE performed showed an EF of 15%. He was diuresed 25 L during that stay. His heart failure was medically managed. We present this case of dilated cardiomyopathy secondary to acute pancreatitis.